Elevated markers of liver function are associated with poorer outcomes in HFREF: an analysis of DAPA-HF. (14th October 2021) - Cowan, L; Adamson, C; Docherty, K; Inzucchi, S; Koeber, L; Kosiborod, M; Martinez, F; Ponikowski, P; Sabatine, M; Solomon, S; Bengtsson, O; Sjostrand, M; et al.
Abstract: Background: Abnormalities of liver tests in patients with heart failure with reduced ejection fraction (HFrEF) is a well-recognised phenomenon. We examined the prognostic value of measures of liver function in a large contemporary cohort of patients with HFrEF enrolled in the Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure (DAPA-HF) trial Methods: In this post-hoc analysis of the DAPA-HF trial we studied 4625 patients with liver function tests available at baseline. Cox proportional hazards models were used to assess the association between liver tests (total bilirubin, alkaline phosphatase [ALP], alanine transaminase [ALT], aspartate transaminase [AST]) and the Model for End-stage Liver Disease excluding INR (MELD-XI) score (calculated as 5.11 Ln [total bilirubin as mg/dL] + 11.76 Ln [creatinine as mg/dL] + 9.44), and the risk of the primary composite endpoint (hospitalisation or urgent visit for heart failure or cardiovascular death). Models were adjusted for age, sex, race, region, systolic blood pressure, heart rate, LVEF, eGFR, log-transformed NT-proBNP, NYHA class, history of hypertension, stroke, myocardial infarction, atrial fibrillation, heart failure aetiology and randomized treatment to dapagliflozin and stratified by diabetic status at baseline. An interaction term between each measure and the effect of treatment on the primary composite outcome was tested as a fractional polynomial. Results: Total bilirubin, ALP, and MELD-XI score were associated with a higher risk of all the primary outcome (Figure 1) but not ALT or AST. These relationships persisted after adjustment: total bilirubin per log unit increase (HR=1.46; 95% CI 1.28 – 1.67, p<0.001), ALP per log unit increase (HR=1.39; 95% CI 1.15 – 1.66, p<0.001), MELD-XI per 1 SD increase (HR 1.27; 95% CI 1.13 – 1.42, p<0.001). The effect of dapagliflozin on the primary outcome was not modified by the baseline levels of either total bilirubin, ALP or MELD-XI score (Figure 2) Conclusions: Higher total bilirubin, ALP and MELD-XI score were independently associated with a higher risk of cardiovascular death or worsening HF and may be useful routinely available biomarkers to assess prognosis. The efficacy of dapagliflozin was the not modified by baseline levels of any of these markers. Funding Acknowledgement: Type of funding sources: None.